Evaluation of the RIFER procedure in treating high intersphincteric anal fistulas - Ding, Yan; Xue, Yahong; Miao, Yaqiu; Zhu, Huiting; Ye, Rui; Wang, Xiaofeng (Frontiers in Medicine, 2025)
IntroductionA high intersphincteric anal fistula is a common anorectal disease that is challenging to treat due to high recurrence rates and has the risk of sphincter damage, which can lead to incontinence. This study aimed to evaluate the efficacy and safety of the rectal incision, fistula excision, and reconstruction (RIFER) procedure for treating high intersphincteric anal fistulas.MethodsTwenty-six patients with high intersphincteric anal fistulas who were admitted to Nanjing Hospital of Traditional Chinese Medicine between September 2021 and March 2024 and underwent the RIFER procedure were included. Patients were followed up for 6 months, and treatment efficacy, recurrence, and postoperative complications after the RIFER procedure were assessed.ResultsThe surgical cure rate of patients treated with RIFER was 100%, with no recurrence or postoperative complications during the follow-up period. The average wound-healing time was 45.40 days. Functional scoring indicators, such as the visual analog and Wexner anal function scores, improved at different postoperative time points. After the RIFER procedure, the incision scar score of most patients (18 of 25) was 0, and none of the patients reported keyhole-like anal deformities. The mean hospital stay was 10.15 days.ConclusionThe RIFER procedure demonstrated remarkable efficacy and safety in the treatment of high intersphincteric anal fistulas, with no recurrence or postoperative complications. This procedure is suitable for treating high intersphincteric anal fistulas in clinical practice.